Hard Coat Film

The hard coat film, featuring a substrate film and a hard coat layer made from an ionizing radiation curable resin and a damping agent, addresses the vulnerability of flexible displays to local external forces by enhancing hardness and impact resistance.

JP7669037B2Active Publication Date: 2025-04-28HIGASHIYAMA FILM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021212105
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-27
Publication Date
2025-04-28
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

Flexible displays without a glass substrate are prone to damage from local external forces, such as pointed objects, due to their lack of protection.

Method used

A hard coat film with a substrate film and a hard coat layer formed from a cured product of a resin composition containing an ionizing radiation curable resin and a damping agent, such as diphenylamine or bisphenol compounds, to enhance hardness and impact resistance.

Benefits of technology

The hard coat film achieves good hardness and scratch resistance, effectively suppressing damage to the display even when local external forces are applied, while maintaining high impact resistance and scratch resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669037000002
    Figure 0007669037000002
  • Figure 0007669037000003
    Figure 0007669037000003
  • Figure 0007669037000004
    Figure 0007669037000004
Patent Text Reader

Abstract

To provide a hard coat film that can prevent a display from being broken even in a case where a local external force is applied while having favorable hardness and scratch resistance.SOLUTION: A hard coat film 10 includes a base material film 12, and a hard coat layer 14 formed on a surface of the base material film 12. The hard coat layer 14 is formed of a cured product of a resin composition containing an ionization radiation curable resin and a damping property-imparting agent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard coat film, and more specifically to a hard coat film used on the display surface of a liquid crystal display, an organic EL display, a touch panel provided in a smartphone, or the like. [Background technology]

[0002] Hard coat films are used for the purpose of protecting the displays of image display devices such as liquid crystal display devices and organic electroluminescence display devices. In recent years, in the field of image display devices, flexible displays that can maintain their display function even when bent and can be repeatedly bent and used have attracted attention. As flexible displays, foldable displays that can be folded and rollable displays that can be rolled into a cylindrical shape are known. Flexible displays are expected to be used in mobile terminals such as smartphones and tablet terminals, and stationary displays that can be stored. As the cover window of a flexible display, an easily bendable ultra-thin glass film (UTG) or a plastic film is used instead of the plate-shaped glass substrate that has been widely used in conventional display devices.

[0003] Since UTG and plastic films are more susceptible to scratches than glass substrates, there is an increasing demand for hard coat films on which a hard coat layer is formed to protect the surface of UTG and plastic films. In many cases, hard coat films are attached to the front window or retardation film of a display via an optical adhesive layer (OCA). For example, Patent Document 1 discloses a hard coat film in which a hard coat layer is laminated on a polyimide film. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-122583 A Summary of the Invention [Problem to be solved by the invention]

[0005] In flexible displays such as those described above, since the surface is not covered with a glass substrate, there is an issue that the display may be relatively easily damaged when a localized external force is applied, for example, when it is hit by a sharp object such as a ballpoint pen. An object of the present invention is to provide a hard coat film that has good hardness and scratch resistance, and is capable of suppressing damage to a display even when a localized external force is applied thereto. [Means for solving the problem]

[0006] In order to achieve the above object, the hard coat film according to the present invention has the following configuration. The hard coat film according to the present invention has a base film and a hard coat layer formed on a surface of the base film, and the hard coat layer is formed from a cured product of a resin composition containing an ionizing radiation curable resin and a damping agent.

[0007] Here, the damping agent may be one or more compounds selected from the group consisting of diphenylamine compounds and bisphenol compounds. The damping agent may be one or more compounds selected from the group consisting of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, p-(p-toluenesulfonylamido)diphenylamine, octylated diphenylamine, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), and 4,4'-thiobis(3-methyl-6-tert-butylphenol). The content of the damping agent may be 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the ionizing radiation curable resin.

[0008] The substrate film may have a transparent adhesive layer on the surface opposite to the hard coat layer, and a protective film may be provided on the surface of the hard coat layer. Effect of the Invention

[0009] The hard coat film according to the present invention has a substrate film and a hard coat layer formed on the surface of the substrate film. The hard coat layer is formed from a cured product of a composition for forming a hard coat layer, which contains an ionizing radiation curable resin and a damping property imparting agent. Therefore, while having good hardness and scratch resistance, damage to the display can be suppressed even when a localized external force is applied.

[0010] Here, when the damping agent is one or more compounds selected from the group consisting of diphenylamine compounds and bisphenol compounds, the effect of suppressing damage to the display when a local external force is applied is particularly excellent. In addition, the compounds listed above can be suitably applied as such damping agents. When the content of the damping agent is 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the ionizing radiation curable resin, the hard coat layer can achieve a high degree of both impact resistance and scratch resistance.

[0011] When the substrate film has a transparent adhesive layer on the surface opposite to the hard coat layer, the hard coat film can be attached to the surface of the display with good adhesion and the glass of the display can be prevented from scattering. Also, when a protective film is provided on the surface of the hard coat layer, the surface of the hard coat layer can be prevented from being scratched during the processing and lamination of the hard coat film. [Brief description of the drawings]

[0012] [Figure 1] 1 is a schematic cross-sectional view of a hard coat film according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a hard coat film according to a second embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view of a hard coat film according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below.

[0014] [Hardcoat film according to the first embodiment] 1 is a cross-sectional view of a hard coat film according to a first embodiment of the present invention. As shown in FIG 1, a hard coat film 10 according to the first embodiment of the present invention has a base film 12 and a hard coat layer 14 formed on the surface of the base film 12.

[0015] <Base film> The specific configuration of the base film 12 is not particularly limited as long as it has transparency. Examples of the base film 12 include a transparent polymer film and a glass film. Transparency means that the total light transmittance in the visible light wavelength region is 50% or more, and the total light transmittance is more preferably 85% or more. The total light transmittance can be measured in accordance with JIS K7361-1 (1997). The thickness of the base film 12 is not particularly limited, but is preferably in the range of 12 μm or more and 200 μm or less from the viewpoints of handling, colorless transparency, and bending property. More preferably, it is 20 μm or more, and particularly preferably 25 μm or more. Also, it is more preferably 100 μm or less, and particularly preferably 80 μm or less. Note that the term "film" generally refers to a film having a thickness of less than 0.25 mm, but even if the thickness is 0.25 mm or more, if it can be wound into a roll, it is included in the "film" even if the thickness is 0.25 mm or more.

[0016] When the base film 12 is a transparent polymer film, examples of the polymer material constituting the base film 12 include polyester resins such as polyethylene terephthalate resin and polyethylene naphthalate resin, polycarbonate resin, poly(meth)acrylate resin, polystyrene resin, polyamide resin, polyimide resin, polyacrylonitrile resin, polypropylene resin, polyethylene resin, polycycloolefin resin, cycloolefin copolymer resin, and other polyolefin resins, cellulose-based resins such as triacetyl cellulose resin and diacetyl cellulose resin, polyphenylene sulfide resin, polyvinyl chloride resin, polyvinylidene chloride resin, and polyvinyl alcohol resin. The polymer material of the base film 12 may be composed of only one of these materials, or may be composed of a combination of two or more of them. Among these, polyethylene terephthalate resin, polyimide resin, aromatic polyamide resin, polycarbonate resin, poly(meth)acrylate resin, polycycloolefin resin, cycloolefin copolymer resin, and triacetyl cellulose resin are more preferable from the viewpoint of optical properties and durability.

[0017] The base film 12 may be composed of a single layer containing one or more of the above-mentioned polymeric materials, or may be composed of two or more layers, such as a layer containing one or more of the above-mentioned polymeric materials and a layer containing one or more of a different polymeric material.

[0018] <Hard coat layer> The hard coat layer 14 is formed from a cured product of a resin composition for forming a hard coat layer, which contains an ionizing radiation curable resin and a damping agent.

[0019] (ionizing radiation curable resin) The hard coat layer 14 is composed of a cured product of a curable composition containing an ionizing radiation curable resin from the viewpoints of high hardness, high flexibility, productivity, etc. Ionizing radiation refers to electromagnetic waves or charged particle beams that have an energy quantum capable of polymerizing or crosslinking molecules. Examples of ionizing radiation include electromagnetic waves such as ultraviolet rays (UV), X-rays, and gamma rays, and charged particle beams such as alpha rays, electron beams (EB), and ion beams. Of these, ultraviolet rays (UV) are particularly preferred from the viewpoint of productivity.

[0020] The ionizing radiation curable resin contains at least one of monomers, oligomers, and prepolymers having a reactive group reactive to ionizing radiation. Examples of the reactive group reactive to ionizing radiation include radical polymerization type reactive groups having an ethylenically unsaturated bond, such as acryloyl group, methacryloyl group, allyl group, and vinyl group, and cationic polymerization type reactive groups, such as oxetanyl group. Among these, acryloyl group, methacryloyl group, and oxetanyl group are more preferred, and acryloyl group and methacryloyl group are particularly preferred. That is, as the ionizing radiation curable resin, (meth)acrylate is particularly preferred. In this specification, "(meth)acrylate" means "at least one of acrylate and methacrylate". "(meth)acryloyl" means "at least one of acryloyl and methacryloyl". "(meth)acrylic" means "at least one of acrylic and methacrylic".

[0021] The (meth)acrylate constituting the ionizing radiation curable resin may be composed of only a monofunctional (meth)acrylate, may be composed of only a polyfunctional (meth)acrylate, or may be composed of a combination of a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. It is more preferable that the composition cured by ionizing radiation contains a polyfunctional (meth)acrylate.

[0022] Examples of the (meth)acrylate include urethane (meth)acrylate, silicone (meth)acrylate, alkyl (meth)acrylate, aryl (meth)acrylate, etc. Among them, urethane (meth)acrylate is particularly preferable from the viewpoint of being relatively flexible and improving the bending property of the hard coat film 10.

[0023] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, bornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, di Cyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate, 2-naphthylmethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy-2-methylethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 3-phenoxy-2-hydroxypropyl (meth)acrylate, 2-phenylphenoxyethyl (meth)acrylate, 4-phenylphenoxyethyl (meth)acrylate, (meth)acrylate, 3-(2-phenylphenyl)-2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxyethylene glycol (meth)acrylate,Examples of the methacrylate include ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.

[0024] Examples of the polyfunctional (meth)acrylate include a bifunctional (meth)acrylate, a trifunctional (meth)acrylate, a tetrafunctional (meth)acrylate, etc. More specifically, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc. pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tripentaerythritol octa(meth)acrylate.

[0025] Examples of oligomers and prepolymers include urethane (meth)acrylates, silicone (meth)acrylates, alkyl (meth)acrylates, aryl (meth)acrylates, etc. Other examples include polymers having a reactive group reactive to ionizing radiation.

[0026] The (meth)acrylate of the ionizing radiation curable resin may be composed of one kind of the above-mentioned (meth)acrylate alone, or may be composed of two or more kinds.

[0027] (damping agent) The damping agent contained in the hard coat layer contributes to improving the impact resistance of the hard coat layer.

[0028] Damping agents are substances that have a polarization (positive / negative bias) called a dipole that rotates (at the resonant frequency) when energy such as sound, vibration, electromagnetic waves, or impact is applied as an external force. When sound, vibration, or electromagnetic waves hits this substance, the dipole moves or rotates, and frictional heat is generated by collisions between the molecular chains of the matrix and between the dipoles, which is converted into thermal energy and attenuates the applied energy. The efficiency of this energy conversion depends on the magnitude of the dipole moment. For example, the effect of this can be seen in the principle of a microwave oven, where water molecules (H2O), which has the highest dipole moment of any substance, rotate and generate heat when microwaves are applied to them.

[0029] Examples of damping agents having such an action and suitable for addition to the composition constituting the hard coat layer 14 include diphenylamine compounds, bisphenol compounds, benzothiazole compounds, benzotriazole compounds, benzophenone compounds, etc. Among them, it is preferable to use one or more compounds selected from the group consisting of diphenylamine compounds and bisphenol compounds.

[0030] Examples of diphenylamine compounds include 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, p-(p-toluenesulfonylamide)diphenylamine, and octylated diphenylamine. Examples of bisphenol compounds include 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), and 4,4'-thiobis(3-methyl-6-tert-butylphenol). Among these, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine and 4,4'-butylidenebis(3-methyl-6-tert-butylphenol) are particularly preferred from the viewpoint of compatibility with ionizing radiation curable resins.

[0031] A hard coat layer having impact resistance can be obtained by blending a damping agent with high dipole efficiency into a matrix made of an ionizing radiation curable resin. When an impact force is applied from the outside to the impact-resistant hard coat layer 14 made of such a damping agent, the dipoles present inside the resin matrix are displaced. The displacement of the dipoles means that each dipole inside the resin matrix rotates or the phase shifts.

[0032] The arrangement of dipoles inside the resin matrix before the application of an impact force (impact energy) can be said to be in an energetically stable state. However, the application of an impact force (impact energy) causes a displacement of the dipoles present inside the resin matrix, which places each dipole inside the resin matrix in an unstable state. Each dipole then tries to return to its original stable state. At this time, Joule heat is generated due to contact between the substance having the dipole and the adjacent polymer chains or low molecules, and as a result, the energy added by the impact is converted into thermal energy and disappears. It is believed that the effect of absorbing the impact force occurs through the displacement of the dipoles inside the resin matrix and the subsequent energy consumption due to the restoration action of the dipoles.

[0033] The content of the damping agent in the composition constituting the hard coat layer 14 is preferably 1 part by mass or more relative to 100 parts by mass of the ionizing radiation curable resin. If it is 1 part by mass or more, the impact resistance is sufficient. From this viewpoint, it is more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more. On the other hand, the content of the damping agent is preferably 20 parts by mass or less. If it is 20 parts by mass or less, the scratch resistance of the surface of the hard coat layer 14 can be made good. From this viewpoint, it is more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less. In the hard coat layer 14, the damping agent is distributed in a dispersed state in the cured product of the ionizing radiation curable resin.

[0034] (Other Ingredients) The composition cured by ionizing radiation constituting the hard coat layer 14 may or may not contain a polymer that is not cured by ionizing radiation in addition to the polymer that is cured by ionizing radiation. The composition cured by ionizing radiation may also contain a polymerization initiator. If necessary, additives that can be generally added to curable compositions may also be contained. Examples of additives include dispersants, leveling agents, defoamers, thixotropic agents, antifouling agents, antibacterial agents, flame retardants, slip agents, inorganic particles, and resin particles. If necessary, a solvent may also be contained.

[0035] Polymers that are not cured by ionizing radiation include thermoplastic resins, thermosetting resins, etc. Thermoplastic resins include polyester resins, polyether resins, polyolefin resins, polyamide resins, (meth)acrylic resins, etc. Thermosetting resins include unsaturated polyester resins, epoxy resins, alkyd resins, phenolic resins, etc.

[0036] The polymerization initiator may be a photopolymerization initiator. The photopolymerization initiator may be an alkylphenone-based, acylphosphine oxide-based, or oxime ester-based photopolymerization initiator. The alkylphenone-based photopolymerization initiator may be 2,2'-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl ... Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the oxime ester photopolymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime), ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), etc. The photopolymerization initiator may be used alone or in combination of two or more of them.

[0037] The content of the photopolymerization initiator is preferably 0.1% by mass or more, more preferably 1% by mass or more, based on the total amount of the composition that is cured by ionizing radiation, while the content is preferably 10% by mass or less, more preferably 5% by mass or less.

[0038] The inorganic particles and resin particles are added to the hard coat layer 14 for the purpose of, for example, preventing blocking of the hard coat layer 14, suppressing wrinkles, improving the surface hardness, etc. The inorganic particles or resin particles added form fine surface irregularities in the hard coat layer 14, which makes it easier to suppress blocking, which occurs when the front and back surfaces of the hard coat film 10 are adhered to each other, when the hard coat film 10 is wound or stacked in a roll shape.

[0039] The composition that is cured by ionizing radiation may be diluted with a solvent. Examples of the solvent include alcohol-based solvents such as ethanol, isopropyl alcohol (IPA), n-butyl alcohol (NBA), ethylene glycol monomethyl ether (EGM), ethylene glycol monoisopropyl ether (IPG), propylene glycol monomethyl ether (PGM), and diethylene glycol monobutyl ether; ketone-based solvents such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclohexanone, and acetone; aromatic solvents such as toluene and xylene; ester-based solvents such as ethyl acetate (EtAc), propyl acetate, isopropyl acetate, and butyl acetate (BuAc); and amide-based solvents such as N-methylpyrrolidone, acetamide, and dimethylformamide. These may be used alone or in combination as a solvent.

[0040] The solids concentration (concentration of components other than the solvent) of the composition that is cured by ionizing radiation may be appropriately determined in consideration of coatability, film thickness, etc. For example, it may be 1 mass % or more, 1.5 mass % or more, 2 mass % or more, etc. Also, it may be 90 mass % or less, 80 mass % or less, 70 mass % or less, etc.

[0041] (Thickness and hardness of hard coat layer) The thickness of the hard coat layer 14 is not particularly limited, but is preferably 0.5 μm or more from the viewpoint of having sufficient hardness. More preferably, it is 1.0 μm or more, and even more preferably, it is 3.0 μm or more. Also, from the viewpoint of easily suppressing curling due to the difference in thermal shrinkage with the base film 12, it is preferably 10 μm or less. More preferably, it is 8.0 μm or less, and even more preferably, it is 6.0 μm or less. The thickness of the hard coat layer 14 is the thickness of a relatively smooth portion in a portion without irregularities due to inorganic particles or resin particles in the thickness direction.

[0042] The hard coat layer 14 preferably has a pencil hardness of HB or more. More preferably, it is H or more. The pencil hardness of the hard coat layer 14 referred to here is the pencil hardness of the surface of the hard coat layer 14 formed on one side of the base film 12, and is measured in a state where a transparent adhesive layer 22 (described later) is not formed on the other side of the base film 12. The pencil hardness of the hard coat layer 14 can be measured in accordance with JIS K 5600-5-4.

[0043] <Method of manufacturing hard coat film> The hard coat film 10 can be produced by coating a composition that will become the hard coat layer 14 on the surface of the base film 12, drying it as necessary, and then curing it by exposure to ionizing radiation such as ultraviolet light to form the hard coat layer 14 on the surface of the base film 12. In this case, in order to improve the adhesion between the base film 12 and the hard coat layer 14, the surface of the base film 12 may be subjected to a surface treatment before coating. Examples of the surface treatment include corona treatment, plasma treatment, hot air treatment, ozone treatment, and ultraviolet treatment.

[0044] The composition that forms the hard coat layer 14 can be applied by various coating methods, such as reverse gravure coating, direct gravure coating, die coating, bar coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, and kiss coating, or various printing methods, such as inkjet printing, offset printing, screen printing, and flexographic printing.

[0045] The conditions for the drying step are not particularly limited as long as the solvent used in the coating liquid can be removed, but it is preferable to perform the drying step at a temperature of 50° C. to 150° C. for 10 seconds to 180 seconds. In particular, the drying temperature is preferably 50° C. to 120° C.

[0046] For ultraviolet irradiation, a high-pressure mercury lamp, an electrodeless (microwave type) lamp, a xenon lamp, a metal halide lamp, or any other ultraviolet irradiation device can be used. If necessary, ultraviolet irradiation may be performed under an inert gas atmosphere such as nitrogen. The amount of ultraviolet irradiation is not particularly limited, but is preferably 50 to 800 mJ / cm. 2 is preferable, and 100 to 300 mJ / cm 2 is more preferred.

[0047] The hard coat film 10 having the above-mentioned configuration is a hard coat film having a base film 12 and a hard coat layer 14 formed on the surface of the base film 12. Since the hard coat layer 14 contains a binder resin and a damping agent, the hard coat film 10 has excellent impact resistance and scratch resistance.

[0048] [Hardcoat film according to another embodiment] The hard coat film according to the present invention is not limited to the configuration of the hard coat film 10 according to the first embodiment. Other embodiments of the hard coat film according to the present invention will be described below.

[0049] Second Embodiment FIG. 2 shows a hard coat film 20 according to the second embodiment having a transparent adhesive layer 22 as an optically adhesive layer (OCA). The hard coat film 20 according to the second embodiment has a base film 12 and a hard coat layer 14 formed on one surface of the base film 12. The hard coat film 20 also has a transparent adhesive layer 22 on the other surface of the base film 12. A release film 24 is disposed on the surface of the transparent adhesive layer 22 as necessary. The release film 24 functions as a protective layer for the transparent adhesive layer 22 before use, and is peeled off from the transparent adhesive layer 22 when in use.

[0050] The hard coat film 20 of the second embodiment differs from the hard coat film 10 of the first embodiment in that it has a transparent adhesive layer 22 on the other side of the base film 12, but is otherwise similar to the hard coat film 10 of the first embodiment, and a description of the similar configuration will be omitted.

[0051] The transparent adhesive layer 22 is for attaching the hard coat film 20 to the surface of the display with good adhesion. In addition, the hard coat film 20 has an effect of preventing the glass of the display from shattering by having the transparent adhesive layer 22. That is, the hard coat film 20 also functions as a shatterproof film.

[0052] The adhesive composition forming the transparent adhesive layer 22 may contain a known adhesive resin such as a (meth)acrylic adhesive, a silicone adhesive, or a urethane adhesive. Among them, a (meth)acrylic adhesive is preferred from the viewpoint of optical transparency and heat resistance. The adhesive composition preferably contains a crosslinking agent to increase the cohesive force of the transparent adhesive layer 22. Examples of the crosslinking agent include an isocyanate crosslinking agent, an epoxy crosslinking agent, an aziridine crosslinking agent, and a chelate crosslinking agent.

[0053] The pressure-sensitive adhesive composition may contain additives as necessary. Examples of additives include known additives such as plasticizers, silane coupling agents, surfactants, antioxidants, fillers, curing accelerators, and curing retarders. In addition, from the viewpoint of productivity, the pressure-sensitive adhesive composition may be diluted with an organic solvent.

[0054] The thickness of the transparent adhesive layer 22 is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less.

[0055] The transparent adhesive layer 22 can be formed by a method of directly applying an adhesive composition onto the other side of the base film 12, a method of applying an adhesive composition onto the side of a release film 24 and then transferring it onto the other side of the base film 12, or a method of applying an adhesive composition onto the side of a first release film and then laminating a second release film, peeling off one of the release films, and transferring it onto the other side of the base film 12.

[0056] The shear storage modulus of the transparent adhesive layer 22 at 25° C. is preferably 1.0×10 4 Pa or more, preferably 2.0×10 4 Pa or more, more preferably 5.0×10 4 Pa or more, particularly preferably 1.0×10 5 Pa or more, preferably 3.0×10 6 Pa or less, more preferably 2.0×10 6 Pa or less, more preferably 1.0×10 6 Pa or less. The shear storage modulus (G') is 1.0×10 4 If the pressure is 3.0×10 Pa or more, the transparent adhesive layer 22 can have a suitable flexibility and shape conformability while having good impact resistance. 6 If it is less than Pa, the cohesive force and adhesiveness of the transparent adhesive layer 22 will be better.

[0057] From the viewpoint of preventing lifting or peeling, the transparent adhesive layer 22 preferably has an adhesive strength to an adherend of 4 N / 25 mm or more, more preferably 6 N / 25 mm or more, and further preferably 10 N / 25 mm or more.

[0058] <Third embodiment> 3 shows a hard coat film 30 according to the third embodiment having a protective film. The hard coat film 30 according to the third embodiment has a base film 12, a hard coat layer 14 formed on one surface of the base film 12, and a protective film 28 arranged on the surface of the hard coat layer 14 via an adhesive layer 26. The base film 12 also has a transparent adhesive layer 22 on the other surface. A release film 24 is arranged on the surface of the transparent adhesive layer 22 as necessary.

[0059] The hard coat film 30 of the third embodiment differs from the hard coat film 20 of the second embodiment in that it has a protective film 28 on the surface of the hard coat layer 14 via an adhesive layer 26, but is otherwise similar to the hard coat film 20 of the second embodiment, and a description of the similar configuration will be omitted.

[0060] The protective film 28 can prevent the surface of the hard coat layer 14 from being scratched when the hard coat film 30 is handled, for example, by continuous processing in a roll process or by bonding to a touch panel. The protective film 28 is attached to the surface of the hard coat layer 14 via the adhesive layer 26. After processing or bonding of the hard coat film 30, the protective film 28 is peeled off from the surface of the low refractive index layer 14 together with the adhesive layer 26. For this reason, the adhesive layer 26 is adjusted so that the adhesive strength between the protective film 28 and the adhesive layer 26 is stronger than the adhesive strength between the hard coat layer 14 and the adhesive layer 26, and the adhesive strength between the hard coat layer 14 and the adhesive layer 26 is capable of interfacial peeling.

[0061] The material constituting the protective film 28 can be appropriately selected from those exemplified as the material constituting the base film 12. The thickness of the protective film 28 is not particularly limited, but can be within a range of 2 μm or more and 500 μm or less, further 200 μm or less.

[0062] The adhesive forming the adhesive layer 26 is not particularly limited, and (meth)acrylic adhesives, silicone adhesives, urethane adhesives, etc. can be suitably used. In particular, acrylic adhesives are suitable because of their excellent transparency and heat resistance. The (meth)acrylic adhesive is preferably formed from an adhesive composition containing a (meth)acrylic polymer and a crosslinking agent.

[0063] The (meth)acrylic polymer is a homopolymer or copolymer of a (meth)acrylic monomer. Examples of the (meth)acrylic monomer include an alkyl group-containing (meth)acrylic monomer, a carboxyl group-containing (meth)acrylic monomer, and a hydroxyl group-containing (meth)acrylic monomer.

[0064] Examples of the alkyl group-containing (meth)acrylic monomer include (meth)acrylic monomers having an alkyl group having 2 to 30 carbon atoms. The alkyl group having 2 to 30 carbon atoms may be linear, branched, or cyclic. More specific examples of the alkyl group-containing (meth)acrylic monomer include isostearyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, decyl (meth)acrylate, isononyl (meth)acrylate, nonyl (meth)acrylate, isooctyl (meth)acrylate, octyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, propyl (meth)acrylate, ethyl (meth)acrylate, and methyl (meth)acrylate.

[0065] Examples of the carboxyl group-containing (meth)acrylic monomer include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, etc. The carboxyl group may be located at the end of the alkyl chain or in the middle of the alkyl chain.

[0066] Examples of hydroxyl group-containing (meth)acrylic monomers include hydroxylauryl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, etc. The hydroxyl group may be located at the end of the alkyl chain or in the middle of the alkyl chain.

[0067] The (meth)acrylic monomer forming the (meth)acrylic polymer may be any one of the above or a combination of two or more thereof.

[0068] Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, a metal chelate-based crosslinking agent, a metal alkoxide-based crosslinking agent, a carbodiimide-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a melamine-based crosslinking agent, etc. The crosslinking agent may be used alone or in combination of two or more.

[0069] The adhesive composition may contain other additives in addition to the (meth)acrylic polymer and the crosslinking agent. Examples of other additives include crosslinking accelerators, crosslinking retarders, tackifiers, antistatic agents, silane coupling agents, plasticizers, peeling aids, pigments, dyes, wetting agents, thickeners, UV absorbers, preservatives, antioxidants, metal deactivators, alkylating agents, and flame retardants. These are appropriately selected and used depending on the application and purpose of the adhesive.

[0070] The thickness of the adhesive layer 26 is not particularly limited, but is preferably 1 μm or more, more preferably 2 μm or more, and is preferably 10 μm or less, more preferably 7 μm or less.

[0071] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the present invention. For example, in the above embodiment, it is described that the surface of the base film 12 may be subjected to a surface treatment, but instead of the surface treatment, a configuration in which an easy-adhesion layer is provided on the surface of the base film 12 may be used. In addition, various functional layers such as a gas barrier improving layer, an antistatic layer, and an oligomer block layer may be provided on the surface of the base film 12 before the hard coat layer 14 is formed. In addition, various functional layers such as a transparent conductive layer, an antiglare layer, an antireflection layer, an antistatic layer, an antifouling layer, and an antifogging layer may be provided on the surface of the hard coat layer 14. EXAMPLES

[0072] The present invention will be described in detail below with reference to examples and comparative examples. Unless otherwise specified, each step of preparing and evaluating a sample is carried out in air at room temperature.

[0073] <Preparation of hard coat layer forming composition> (Examples 1 to 2) A hard coat layer-forming composition was prepared by adding 4,4'-butylidenebis(3-methyl-6-tert-butylphenol) (Ouchi Shinko Chemical's "Nocrac NS-30", melting point: 208°C) as a damping agent 1 and a photopolymerization initiator "Omnirad127" (IGM Resins BV) to an ultraviolet-curable resin composition (DIC's "ESS-620", urethane acrylate resin, solvent: ethyl acetate, solid content concentration: 79% by mass). At this time, the amount of the damping agent was as shown in Table 1 (parts by mass relative to 100 parts by mass of the solid content of the ultraviolet-curable resin), and the amount of the photopolymerization initiator was 3% by mass relative to 100% by mass of the solid content of the ultraviolet-curable resin and the damping agent. Furthermore, ethyl acetate was added to the hard coat layer-forming composition so that the solid content concentration was 42.5% by mass.

[0074] (Examples 3 to 4) <Preparation of hard coat layer forming composition> The compositions for forming hard coat layers of Examples 3 and 4 were prepared in the same manner as in Examples 1 and 2 above, except that 4,4'-bis(α,α-dimethylbenzyl)diphenylamine (Nocrac CD, manufactured by Ouchi Shinko Chemical Co., Ltd., melting point: 90°C) was used as damping agent 2 instead of damping agent 1.

[0075] Comparative Example 1 A composition for forming a hard coat layer of Comparative Example 1 was prepared in the same manner as in Examples 1 to 4, except that no damping agent was used.

[0076] <Formation of hard coat layer> Each of the compositions for forming a hard coat layer prepared above was applied to a substrate film (Toyobo's polyethylene terephthalate film "TA048", thickness 80 μm) using a #12 wire bar, dried at 80°C for 60 seconds, and then irradiated with a high-pressure mercury lamp with a light intensity of 200 mJ / cm. 2 A hard coat layer (film thickness: 5 μm) was formed by irradiating the film with ultraviolet light of 100 .mu.m. In this manner, the hard coat films according to Examples 1 to 4 were produced.

[0077] <Evaluation method> (Film thickness) The thickness of the hard coat layer was measured by spectroscopic interferometry using a Filmetrics F20 film thickness measurement system.

[0078] (Steel wool test) A steel wool test was conducted to evaluate the scratch resistance of the hard coat layer. Using a Gakushin-type friction fastness tester (AB-301 COLOR FASTNESS RUBBING TESTER manufactured by Tester Sangyo), steel wool #0000 (manufactured by Nippon Steel Wool Co., Ltd.) fixed to a 20 mm x 20 mm abrader was placed on the surface of the hard coat layer of the hard coat film and reciprocated. The stroke length of the test table was 120 mm, the test table reciprocation speed was 60 reciprocations / min, and the reciprocation was performed with a load of 500 g / cm. The sample was visually observed every 100 reciprocations, and the maximum number of times when no scratches of 10 mm or more in length were observed was taken as the evaluation value of the steel wool test.

[0079] (Pencil hardness of hard coat layer) The hardness of the hard coat layer constituting the hard coat film was measured using a pencil hardness tester (manufactured by Tester Sangyo Co., Ltd.) according to the method specified in JIS K 5600-5-4. The test load was 500g, and the test was repeated five times while changing the pencil hardness. The maximum pencil hardness value at which scratches or dents occurred with the same pencil within one test out of five was taken as the evaluation value.

[0080] (Pen Drop Test) A pen drop test was performed to evaluate the impact resistance of the hard coat layer. The hard coat film was attached to a 2 mm thick glass plate on the side opposite to the hard coat layer via an optical adhesive sheet (Higashiyama Film's "S-PS58", thickness 25 μm) using a hand roller, and the 2 kg roller was rolled back and forth once to bond the film. Next, the hard coat layer was placed on a 5 mm thick SUS plate with the hard coat layer facing up, and a cylinder with a sharpened tip like a pencil (SUS304, diameter φ9 mm, total length 49.8 mm, taper angle 25 °, tip R (radius) 0.8 mm, weight 19.4 g) was dropped from a position 400 mm above the hard coat film so that the sharpened tip would collide perpendicularly with the hard coat layer. Five minutes after the collision test, the depth of the depressions created on the surface of the hard coat film due to the collision was measured using a 3D measurement laser microscope (Olympus's "LEXT OLS5000", objective lens magnification 10 times). Generally, if the depth of the pen drop impact is 50 μm or less, it can be said that the hard coat layer has high impact resistance.

[0081] <Evaluation Results> Table 1 below shows the component composition of the hard coat layer of each sample and the evaluation results.

[0082] [Table 1]

[0083] According to Table 1, in Comparative Example 1, since the hard coat layer does not contain a damping agent, a deep pen drop dent exceeding 50 μm was generated when a localized external force was applied. In contrast, in Examples 1 to 4, in which the hard coat layer contains a damping agent, the depth of the pen drop dent is suppressed to 50 μm or less, and it is understood that the impact resistance of the hard coat layer is improved by adding the damping agent to the hard coat layer. In addition, the evaluation results of the steel wool test and the pencil hardness are almost the same in Examples 1 to 4 and Comparative Example 1, and it is confirmed that the scratch resistance and high hardness of the hard coat layer are maintained even when the damping agent is added.

[0084] As the damping agent, a bisphenol-based compound is used in Examples 1 and 2, and a diphenylamine-based compound is used in Examples 3 and 4. Regardless of which damping agent is used, the impact resistance of the hard coat layer is improved, as evaluated by the reduction in the depth of the pen drop impact mark. Moreover, regardless of which damping agent is used, the effect of improving the scratch resistance is particularly large by increasing the amount of the damping agent added from 2 parts by mass (Examples 1 and 3) to 10 parts by mass (Examples 2 and 4). In particular, the effect is remarkable in Example 4, which uses a diphenylamine-based damping agent.

[0085] As described above, a hard coat film having a base film and a hard coat layer formed on a surface of the base film, in which the hard coat layer is formed from a cured product of a composition for forming a hard coat layer containing an ionizing radiation curable resin and a damping property imparting agent, has good hardness and scratch resistance, and can suppress damage to the display even when a localized external force is applied.

[0086] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and various modifications can be made without departing from the spirit and scope of the present invention. [Explanation of symbols]

[0087] 10,20,30 Hard coat film 12 Base film 14 Hard coat layer 22 Transparent adhesive layer 24 Release film 26 Adhesive layer 28 Protective Film

Claims

1. A substrate film and a hard coat layer formed on a surface of the substrate film, The hard coat film, wherein the hard coat layer is formed from a cured product of a resin composition containing an ionizing radiation curable resin and a damping property imparting agent.

2. 2. The hard coat film according to claim 1, wherein the damping agent is one or more compounds selected from the group consisting of diphenylamine compounds and bisphenol compounds.

3. The attenuation imparting agent is one or more compounds selected from the group consisting of 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, p-(p-toluenesulfonylamide)diphenylamine, octylated diphenylamine, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), and 4,4'-thiobis(3-methyl-6-tert-butylphenol), the hard coat film according to claim 1 or claim 2.

4. 4. The hard coat film according to claim 1, wherein the content of the attenuation agent is 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the ionizing radiation curable resin.

5. The hard coat film according to claim 1 , further comprising a transparent adhesive layer on a surface of the substrate film opposite to the hard coat layer.

6. The hard coat film according to claim 1 , further comprising a protective film on a surface of the hard coat layer.

Citation Information

Patent Citations

  • Damping coating material

    JP2006257235A

  • Hard coat film

    JP2013195549A

  • Damping property imparting agent and damping material

    JP2013199552A

  • Laminate, flexible device, and method for producing laminate

    JP2018122583A

  • Hard coat film and flexible display using the same

    JP2021015168A